2022
DOI: 10.48550/arxiv.2209.08182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Interstellar Interlopers

Abstract: Interstellar interlopers are bodies formed outside of the solar system but observed passing through it. The first two identified interlopers, 1I/'Oumuamua and 2I/Borisov, exhibited unexpectedly different physical properties. 1I/'Oumuamua appeared unresolved and asteroid-like whereas 2I/Borisov was a more comet-like source of both gas and dust. Both objects moved under the action of non-gravitational acceleration. These interlopers and their divergent properties provide our only window so far onto an enormous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 119 publications
1
14
0
Order By: Relevance
“…Tentative constraints on the number density of free-floating icy worlds can be derived by extrapolating microlensing studies to a certain size threshold (Strigari et al 2012;Dai & Guerras 2018); the recent discovery of interstellar planetesimals has furnished additional data (Jewitt & Seligman 2022;Moro-Martín 2022). With regard to icy worlds that are gravitationally bound to stars, their number is sensitive to planetary system architecture, stellar spectral type, and so forth, thereby requiring a statistical (population) study.…”
Section: Model Setupmentioning
confidence: 99%
“…Tentative constraints on the number density of free-floating icy worlds can be derived by extrapolating microlensing studies to a certain size threshold (Strigari et al 2012;Dai & Guerras 2018); the recent discovery of interstellar planetesimals has furnished additional data (Jewitt & Seligman 2022;Moro-Martín 2022). With regard to icy worlds that are gravitationally bound to stars, their number is sensitive to planetary system architecture, stellar spectral type, and so forth, thereby requiring a statistical (population) study.…”
Section: Model Setupmentioning
confidence: 99%
“…Additionally, 'Oumuamua had an extreme shape, a reddened reflection spectrum (Meech et al 2017), and a low incoming velocity indicating a young <40 Myr age (Feng & Jones 2018). Reconciling the lack of activity and the observed nongravitational perturbations remains a challenge (Jewitt & Seligman 2022), even though models have been proposed that could explain all the observed properties of 'Oumuamua, e.g., by assuming a significant presence of molecular hydrogen ice (Seligman & Laughlin 2020). Alternative explanations have invoked the presence of N 2 -and CO-driven activity Seligman et al 2021) or radiation pressure (Micheli et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, the first two interlopers have provided close-up glimpses of extrasolar ejecta. The origin of 1I/'Oumuamua (Williams et al 2017;Meech et al 2017) has been fiercely debated, but each of the hypotheses on its bulk composition points toward previously unconsidered astrophysics in exoplanetary systems (Jewitt & Seligman 2022;Fitzsimmons et al 2023;Seligman & Moro-Martín 2023). Recently, Bergner & Seligman (2023) demonstrated that 'Oumuamua's properties were consistent with an amorphous water ice comet with radiolitically produced H 2 via galactic cosmic rays.…”
Section: Introductionmentioning
confidence: 99%